Methods of translation of cultural terms in the process of literary translation. - Botirova Hakima Abdukodir kizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The current article is devoted to the use of different approaches for translating cultural terms in litarary translation. The art of translation has played and continues to play an important role in the development of world culture. Translation is a growing intellectual activity that translates the charm of one language into another and aims to gain the respect of readers. The concept of culture focuses on three types of human activity: personal because we think and act individually; because we work as a group - collective; because society is self-reflective. Language is social, without which there is no social activity. In the process of translation, we face a foreign culture. For this reason, our success in translation depends on how well we understand the foreign culture, since translation is an intercultural phenomenon. The translation was seen as a means of spreading enlightenment among the peoples, and through it the pursuit of rapprochement with other peoples continued. Until the twentieth century, many cultural, scientific, historical and literary monuments of the peoples of the East were translated into Uzbek.